Ara Mai : an exhibition report presented as partial fulfilment of the requirements for the degree of Masters of Māori Visual Arts, Massey University, Palmerston North, New Zealand - Kauwhata, Deborah Anne (Massey University, 2021)
This exhibition report navigates the ara and the symbolic use within Māori culture as both a journey and an awakening. Critically it addresses the concept of ‘movement’, through the colonised world we currently live in as Māori. The exhibition title ‘Ara Mai’ was intended as a theatrical play on words and concepts that we as Māori continue to act out when in search of self-identity. The works displayed identifies the ara as a relationship and partnership within the world of biculturalism and in particular within the whakapapa of whānau, hapū and marae. Ara Mai is an enticement to encourage te tangata to transverse the ara to finding self, to reconnect to whakapapa, whenua and tikanga Māori. It takes but one step.
Keywords: Māori Masters Thesis; 450721 Ngā toi ataata ngā mahi ā-rehe o te Māori (Māori visual arts and crafts)